The Few Who Made It: Commercially and Clinically Successful Innovative Bone Grafts - Sallent, Ignacio; Capella-Monsonís, Héctor; Procter, Philip; Bozo, Ilia Y.; Deev, Roman V.; Zubov, Dimitri; Vasyliev, Roman; Perale, Giuseppe; Pertici, Gianni; Baker, Justin; Gingras, Peter; Bayon, Yves; et al. (Frontiers in Bioengineering and Biotechnology, 2020)
Bone reconstruction techniques are mainly based on the use of tissue grafts and artificial scaffolds. The former presents well-known limitations, such as restricted graft availability and donor site morbidity, while the latter commonly results in poor graft integration and fixation in the bone, which leads to the unbalanced distribution of loads, impaired bone formation, increased pain perception and risk of fracture, ultimately leading to recurrent surgeries. In the past decade, research efforts have been focused on the development of innovative bone substitutes that not only provide immediate mechanical support, but also ensure appropriate graft anchoring by, for example, promoting de novo bone tissue formation. From the countless studies that aimed in this direction, only few have made the big jump from the benchtop to the bedside, whilst most have perished along the challenging path of clinical translation. Herein, we describe some clinically successful cases of bone device development, including biological glues, stem cell-seeded scaffolds and gene-functionalised bone substitutes. We also discuss the ventures that these technologies went through, the hindrances they faced and the common grounds among them, which might have been key for their success. The ultimate objective of this perspective article is to highlight the important aspects of the clinical translation of an innovative idea in the field of bone grafting, with the aim of commercially and clinically informing new research approaches in the sector.